Effects of cigarette smoking on older chinese men treated with clopidogrel monotherapy or aspirin monotherapy: a prospective study. (3rd July 2020) - Cai, Yulun; Xu, Weihao; Liu, Hongbin; Wang, Fan; Duan, Lei; Li, Huiying; Li, Man; Li, Yuerui; Han, Lina; Xiao, Hunan
Abstract: We investigated the comparative effects of smoking status on outcomes in older Chinese men receiving aspirin or clopidogrel monotherapy. This was a prospective observational study of outcomes in 668 men aged ≥ 60 years undergoing annual health examination in the Chinese People's Liberation Army General Hospital from March–April 2017. All patients received regular treatment with aspirin or clopidogrel. Platelet aggregation and phenotyping for rs762551 were measured in all patients. We recorded all major adverse cardiovascular and cerebrovascular events; namely, all-cause death, myocardial infarction, stroke, transient ischemic attack, and unstable angina. In the clopidogrel subgroup, homozygous carriers (AA) of the CYP1A2*1F gene (rs762551, 163C>A) appeared more frequently in smokers than in nonsmokers (45.6% vs 32.7%, p = .035). Adenosine diphosphate-induced platelet aggregation using light transmittance aggregometry was lower in smokers compared with nonsmokers (44.97 ± 20.05% vs 51.98 ± 19.38%, respectively; p = .0018). Smokers (n = 103) had a decreased risk of major adverse cardiovascular and cerebrovascular events, compared with nonsmokers [n = 159; hazard ratio, 0.466; 95% confidence interval: 0.262–0.829, p = .008]. In the aspirin subgroup, AA-induced platelet aggregation showed no significant difference regarding smoking vs nonsmoking status (30.90 ± 32.21 vs 29.78 ± 31.47, respectively; p = .771). However, we saw a significant increase in adverse clinical events in the smoking group (n = 148) compared with the nonsmoking group (n = 258; hazard ratio = 1.907, 95% confidence interval: 1.128–3.225; p = .016). In older Chinese men, active smokers benefitted from clopidogrel therapy compared with aspirin. Long-term cigarette smoking may contribute to increased variations in CYP1A2*1F, but the variations do not fully explain the smoking paradox.